Nitrofurantoin: properties and potential in treatment of urinary tract infection: a narrative review - Mahdizade Ari, Marzie; Dashtbin, Shirin; Ghasemi, Fatemeh; Shahroodian, Soheila; kiani, Parisa; Bafandeh, Elnaz; Darbandi, Talieh; Ghanavati, Roya; Darbandi, Atieh (Frontiers in Cellular and Infection Microbiology, 2023)
Nitrofurantoin, a wide-spectrum antibiotic accessible since 1953, is utilized widely to treat urinary tract infections as it usually stays active against drug-resistant uropathogen. Nitrofurantoin's use has enhanced exponentially since new guidelines repositioned it as first-line therapy for uncomplicated lower urinary tract infection (UTI). To re-evaluate the first- and second-line therapies for treating uncomplicated UTI, although fluoroquinolones are usually used for this goal, their level of utilization is thought to be inappropriately excessive and will eventually have a detrimental impact; thus, we hypothesize that nitrofurantoin might be the best choice for this sign, because of its low frequency of utilization and its high susceptibility assess in common UTI pathogens. It can be concluded from this review that nitrofurantoin can be considered as the most effective drug in the treatment of acute urinary infection, but due to the long-term side effects of this drug, especially in elderly patients, it is essential to introduce some criteria for prescribing nitrofurantoin in cases of chronic UTI.